Significant enzymatic activities in the residues hydrolysis of the sugar cane harvest (2019)
In the production of ethanol from agroindustrial crop residues, one of the critical stages in the process is the conversion of lignocellulosic material to simple sugars, which can be done chemically or enzymatically. In this research, the enzymatic activities of commercial enzymes were evaluated for their influence on the degradation of lignocellulosic materials from sugar cane harvest residues (leaves and top cane). Eight substrates were pretreated with different delignification methods. Likewise, five enzymatic preparations were configured. An analysis of the enzyme-substrate interactions was conducted through fuzzy system analysis. The results showed regions of maximum enzymatic activity for residues of the sugarcane harvest, between 20-30 Filter Paper Units (FPU) /mL values lower than 500 pNPG (p-Nitrofenol-α-D-Glucopyranoside) U / mL of activity beta-glucosidase and hemicellulase activity between 50 and 70 IU / mL, confirming that the use of large amounts of cellulolytic enzymes is not necessary